COMPARATIVE TRANSCRIPTOME ANALYSIS TO DETERMINE DIFFERENTIALLY EXPRESSED GENES RESPONSIBLE TOWARDS GROWTH OF METROXYLON SAGU - Fifi Hafizzah, Pendi; Yan, Wei Jie; Hasnain, Hussain; Hairul Azman, Roslan; Zainab, Ngaini; Norzainizul, Julaihi (UMT Press, 2025)
: Sago palm (Metroxylon sagu Rottb.) is one of the most important cash crops grown abundantly in Mukah, Sarawak, Malaysia. The palm’s versatility and high starch content led the Sarawak government to introduce large scale commercial sago estate plantations in efforts to boost the local economy. However, several challenges were encountered, including stunted growth (non-trunking) despite the plants reaching maturity. In spite of many researches to address this, information on the molecular mechanisms of sago palms is relatively low. This study compares the transcriptome datasets expressed in trunking sago palms of different localities. The RNA extracted was subjected to RNA sequencing. Raw data was processed with fastp, generating 85.61 Gb clean data, averaging 7 Gb data from each sample. The clean reads were subjected to assembly and mapping using Salmon. Expression count tables were used for DEGs identification using idep.96 webserver. A total of 718 DEGs were commonly expressed in all datasets. Enrichment analysis revealed gene products responsible for maintaining cell stability were enriched in GO, whereas the MAPK and ribosome pathways were significantly enriched in KEGG. The data obtained from this study can be considered for further analysis and understanding, especially toward the genes responsible for normal development in sago palms.